2011
DOI: 10.1155/2011/273907
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Type I Interferon Pathway in Systemic Lupus Erythematosus: Association with Distinct Clinical Phenotypes

Abstract: Growing evidence over the last few years suggests a central role of type I IFN pathway in the pathogenesis of systemic autoimmune disorders. Data from clinical and genetic studies in patients with systemic lupus erythematosus (SLE) and lupus-prone mouse models, indicates that the type I interferon system may play a pivotal role in the pathogenesis of several lupus and associated clinical features, such as nephritis, neuropsychiatric and cutaneous lupus, premature atherosclerosis as well as lupus-specific autoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 129 publications
2
23
0
1
Order By: Relevance
“…This difference may be explained because multiple factors (T and B lymphocytes, cytokines profile, autoantibodies, etc.) are involved in SCNSV in comparison with PCNSV [37][38][39][40]. In support of these findings, the Kaplan-Meier curve after 36 months of follow-up showed a significant difference in the relapse-free survival following 10 months of therapy.…”
Section: Discussionsupporting
confidence: 58%
“…This difference may be explained because multiple factors (T and B lymphocytes, cytokines profile, autoantibodies, etc.) are involved in SCNSV in comparison with PCNSV [37][38][39][40]. In support of these findings, the Kaplan-Meier curve after 36 months of follow-up showed a significant difference in the relapse-free survival following 10 months of therapy.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, activation of type I IFN system has been shown to contribute, at least partially, to accelerated atherosclerosis in SLE patients (22), yet the mechanisms remain to be elucidated. In this study, we confirmed that MIF, a chemokine -like inflammatory regulator related to either atherosclerosis or lupus, was highly expressed in SLE patients, especially those with active diseases.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Here, miR-466l is suggested to be a negative regulator of multiple, proinflammatory IFN-a species. A previous study has also shown that miR-466l enhances the production of immune-suppressive IL-10.…”
Section: Discussionmentioning
confidence: 99%